Síntese e caracterização de geopolímeros à base de metacaulim e micropartículas de vidro soda-cal - Cristiane do Bom Conselho Sales Alvarenga (2018)
Alternative materials, whose production process causes less environmental impact compared to traditional concrete, are the target of research throughout the world. Among these materials include alkali activated compounds with low calcium content, commonly called geopolymers. These binders are obtained by the alkaline activation of materials rich in silica and alumina, with emphasis on the metakaolin and industrial waste. Due to their differentiated properties, aluminosilicates, activated can be used in several applications. Many studies indicate be necessary in addition to metakaolin, silica in the form of sodium or potassium silicates in order to increase the silica content. Whereas the glass waste, on condition of microparticles constitute an environmental liability and are highly reactive and high in silica, your use shall be deemed viable as a source of silica in geopolymers. However, there are still gaps to be clarified, both as regards how to synthesis and characterization. In this sense, this paper evaluates the efficiency of alkaline activation with a focus on the geopolymerization reaction, of metakaolin using potassium silicate, with and without partial replacement of precursor by 12.5% by weight from soda lime microparticles glass amber coloured. The precursors and activated materials were evaluated as to the chemical composition, specific surface, pozolanicity, atomic arrangement and 27Al and 29Si coordinations. The synthesized materials were also evaluated for specific mass and compressive strength. The results indicate that geopolymerization with the use of glass amber soda lime microparticles in place of 12.5% by weight metakaolin is possible. This substitution also favors the mechanical performance of the compounds at 28 days, with an increase of 37% to cure at 40º C and 44% in curing at ambient temperature